ANALISIS USAHATANI SAWI CAISIM DI KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Asty Y. Manu Ndun; Made Tusan Surayasa; Marthen R. Pellokila (Undana Press, 2022)
Research on Analysisof Caisim Mustard Farming in Kupang Tengah District, Kupang Regency has been carried out with the aim of: 1) Analyzing the revenue and income costs of caisim mustard farming in Central Kupang District, Kupang Regency, 2) analyzing the feasibility of caisim mustard farming cultivated by farmers in Central Kupang District. Kupang Regency The research location was chosen intentionally, namely in Noelbaki Village and Oelpuah Village, Central Kupang District, Kupang Regency. Research respondents were caisim mustard farmers who were randomly assigned as many as 40 people. The data collected were analyzed using Cost and Revenue Analysis, as well as Business Feasibility Analysis (R/C Ratioand BEP) The results showed that: 1) the average cost, revenue, and income of caisim mustard farming in Central Kupang District, Kupang Regency were: Rp. 1,054,077,-/are/planting, Rp 1.182.330,-/are/planting, and Rp 128,253/are/planting and 2) Caisim mustard farming cultivated by responden tfarmers in Central Kupang District, Kupang Regency isfeasibletodevelop (R /C Ratio 1.1, BEP Productionandprice<production and selling price